L`opinion des Français sur les Jeux olympiques de Paris 2024 - Collinet, C.; Delalandre, M.; Beaudouin, S. (Movement & Sport Sciences - Science & Motricité, 2020)
The article focuses on the Olympic Games` social legacy. A quantitative survey allows us to assess how the French population perceive the future consequences of the Paris 2024 Olympic Games. The sample consists of 508?individuals aged from 18 to 65. We use a representative sample of the French population in term of age, sex, and social category criteria. The results show that the event creates a real excitement. To define audience some variables, such as sociodemographic particularities and interest in sports activities, are used. It appears that the economic and urban issues are the most feared. Thus, this type of study permits to show the perception, the resistances, hopes and concerns around the events. The survey will be conducted until the event and after in order to better understand its impact over time.